MUSIBAH DALAM PERSPEKTIF AL-QUR’AN (Studi Komparatif Tafsir Ibnu Katsir, Tafsir An-Nur dan Tafsir As-Sa’di) - Sumarni Sumarni; Askahar Askahar; Nurfadillah Syam (Jurnal Ushuluddin Adab dan Dakwah, 2022)
This research discusses that every human being will definitely be given a disaster and that is a certainty. Many verses and hadiths explain the certainty of disaster. Allahﷻ has absolute will and power to give disaster to His servants. Trying to understand the disaster based on the thoughts of Imam Ibnu Katsir, Abdurrahman As-Sa'di and Teungku Muhammad Hasbi. Disaster As for the interpretation of Al-Qur'anul Adzhim, Taisir al-Karim ar-Rahman Fi Tafsir Kalam an-Mannan and Al-Qur'anul Majid An-Nur. The three interpretations were chosen because they have their respective advantages, namely the interpretation of Al-Qur'anul Adzhim bil riwayah interpretation, the interpretation of Taisir al-Karim ar-Rahman Fi The interpretation of Kalam an-Mannan is clear and concise and the interpretation of An-Nur the interpretation of Indonesian which is easy to understand . The background of this research is the number of verses that discuss disasters that are relevant to real life. The focus of the discussion in this study is the similarities and differences in the word calamity in the interpretations of Ibn Katsir, Tafsir An-Nur and Tafsir As-Sa'di as well as the causes and wisdom of calamities in ten verses of calamity namely QS. Al-Baqarah (2):155-157, QS. Al-Imran (3):165, QS. Al Imran (3):165, QS. An-Nisa (4):62, QS. An-Nisa (4): 72, QS. Al Maidah (5): 106, QS. At Tawba (9):50, QS. Al Qashash (28): 47, QS. As-Shura (42):30, QS. Al-Hadid (57):22 and QS. At-Taghabun (64): 11. The methodology used in this research is text research. This type of research uses the library research method of the study of revelation texts, namely research on the texts of the Al-Qur'an, namely examining the verses of the word calamity in the Al-Qur'an. The results of this study indicate that the interpretations of Ibnu Katsir, Tafsir An-Nur and Tafsir As-Sa'di have similarities and differences in understanding the word disaster. In the interpretation of Ibn Kathir he does not explain in detail, he interprets the word disaster as a disaster. whereas in the interpretation of An-Nur he interprets a disaster as a disaster, a threat and punishment, then the interpretation of As-Sa'di interprets it as a disaster and punishment. As for the causes of disasters, namely qada and qadhar Allahﷻ which were written in Lauhul Mahfudz before creating nature, with the permission of Allahﷻ and human actions themselves. As for the meaning of calamity, that is to insult/denounce the hypocrites, to separate those who are honest from those who lie, those who are patient and those who are impatient, not to diminish the faith of a believer or to turn them away from their religion, to teach us to be grateful and patient and pray, a way to get reward, and others.